Theoretical Foundations of Phonostylistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article gives information about phonostylistics, which arose at the junction of phonetics and stylistics. It studies tasks, functions and historical development of phonostylistics.